PENGEMBANGAN MODEL MANAJEMEN SEKOLAH BERBASIS MULTIKULTURAL PADA SEKOLAH MENENGAH ATAS (SMA) DI EKS KARESIDENAN PATI - Su'ad Su'ad (Universitas Muria Kudus, 2017)
School-based management (SBM) creates the quality gap and narrowsthe view of regionalism. Therefore the writer develops a multicultural-based management (MBM) which can accomodate the diversity of the school community. Seven schools have implemented SBM but its functions have not been concern with the diversity of the school community.The formulation of the problems are : 1. how is SBM implemented in senior high schools in the former Pati residency? 2. how is SBM developed into a MBM model in senior high school? This research employed research and development method. Preliminary research applied a qualitative approach that yielded factual picture. The development began with the design of the model validated by experts and produced the model I, then it was brought to Focus Group Discussion and produced Model II which described MBM of senior high school. It is concluded that the development of the school management is a must in order to achieve school goals and it is suggested that 1. Multicultural-based management should be appointed as a national policy in order to achieve a diverse society in schools, 2. MBM policy needs to be followed up with the implementation of multicultural education in a multicultural school.